2009
DOI: 10.1007/s11104-009-0018-x
|View full text |Cite
|
Sign up to set email alerts
|

Root-derived respiration and nitrous oxide production as affected by crop phenology and nitrogen fertilization

Abstract: In annual crops, the partitioning of photosynthates to support root growth, respiration and rhizodeposition should be greater during early development than in later reproductive stages due to source/ sink relationships in the plant. Therefore, seasonal fluctuations in carbon dioxide (CO 2 ) and nitrous oxide (N 2 O) production from roots and root-associated soil may be related to resource partitioning by the crop. Greenhouse studies used 13 C and 15 N stable isotopes to evaluate the carbon (C) partitioning and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
19
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(20 citation statements)
references
References 47 publications
1
19
0
Order By: Relevance
“…Potential denitrification and N 2 O production in soil, as well as the genetic potential for denitrification and N 2 O reduction in both root-associated and soil borne microorganisms, were determined by soil type rather than crop (Table 2). A range of studies showed that N 2 O emissions are higher in cropped soils when compared to bulk soils, thus indicating a significant influence of plants (Ding et al, 2007;H enault et al, 1998;Højberg et al, 1996;Klemedtsson et al, 1987;Ni et al, 2012;Sey et al, 2010;Verma et al, 2006). We observed a similar trend for the potential N 2 O production in soil, although this was not significant (Fig.…”
supporting
confidence: 56%
“…Potential denitrification and N 2 O production in soil, as well as the genetic potential for denitrification and N 2 O reduction in both root-associated and soil borne microorganisms, were determined by soil type rather than crop (Table 2). A range of studies showed that N 2 O emissions are higher in cropped soils when compared to bulk soils, thus indicating a significant influence of plants (Ding et al, 2007;H enault et al, 1998;Højberg et al, 1996;Klemedtsson et al, 1987;Ni et al, 2012;Sey et al, 2010;Verma et al, 2006). We observed a similar trend for the potential N 2 O production in soil, although this was not significant (Fig.…”
supporting
confidence: 56%
“…Second, soil respiration rates (reflecting all heterotrophic and autotrophic respiration) were two to eight times greater than rates of root-derived (heterotrophic) respiration. Rhizosphere respiration (live root plus associated heterotrophic respiration) can contribute substantially to total soil respiration; soybean rhizosphere respiration contributed 40 to 95% of the C respired in a greenhouse study (Sey et al, 2010). Rates of rhizosphere respiration have been shown to increase through the flowering stage of plant development (Fu et al, 2002).…”
Section: Seasonal Patterns Of Rootderived Carbon Cyclingmentioning
confidence: 99%
“…Root biomass depends also on the topographic heterogeneity in R s over the sand dune in phase II. However, from phase II to phase III, additional liable fresh litterfall and suppressed shrub photosynthesis (as declined photosynthetic pigments) results in larger contribution of heterotrophic respiration to total R s (Fu et al, 2002;Sey et al, 2010;Mauritz and Lipson, 2013). Also soil nitrogen content contributes strongly to the litterfall decomposition process (Yan et al, 2010;Sayer et al, 2011).…”
Section: Response Of Spatial Variation In Soil Respiration To Biotic mentioning
confidence: 99%